Multivariate batch to batch optimisation of fermentation processes incorporating validity constraints. (October 2016) - Duran-Villalobos, Carlos A.; Lennox, Barry; Lauri, David
Highlights: A batch-to-batch optimization technique for fermentation processes is proposed. The technique depends on the accuracy of an adaptive MPLS model. Validity constrains were applied to improve consistency. The rate of convergence was found to be slower when using validity constraints. Abstract: This paper presents an innovative optimisation technique, which utilises an adaptive Multiway Partial Least Squares (MPLS) model to track the dynamics of a batch process from one batch to the next. Utilising this model, an optimisation algorithm solves a quadratic cost function that identifies operating conditions for the subsequent batch that should increase yield. Hard constraints are shown to be required when solving the cost function to ensure that batch conditions do not vary too greatly from one batch to the next. Furthermore, validity constraints are imposed to prevent the PLS model from extrapolating significantly when determining new operating conditions. The capabilities of the proposed technique are illustrated through its application to two benchmark fermentation simulations, where its performance is shown to compare favourably with alternative batch-to-batch optimisation techniques.